How is the Psychological Well-Being of the Prospective Counselor: The PERMA-Profiler - Nurmasari, Yessika; Anwar, Moh. Khoerul; Muhsin, Muhsin; Lam, Do Mai (Jurnal Kajian Bimbingan dan Konseling, 2025)
Well-being is one of the factors that prospective counselors continue to develop themselves and their profession. The research aims to provide an overview of the psychological well-being of prospective counselors. The study used the PERMA-Profiler measurement, distributed to Islamic Counseling Guidance students at UIN Sunan Gunung Djati Bandung. The data were analyzed by quantitative descriptive with simple random sampling. The attachment indicator (E) is the largest at 7.48, followed by the positive emotion indicator (P) at 7.44, the meaningfulness indicator (M) with a score of 7.39, the relationship indicator ® with a score of 7.21, the achievement indicator (A) with a score of 7.02. The attachment indicator is the highest, meaning that the prospective counselor is fully involved in the activities being carried out, immersed, and integrated with activities at the university both individually and as a students. The lowest indicator is achievement, described as success in mastering and achieving something. Prospective counselors feel they have not made any achievements because they are still learning about the science of guidance and counseling. Efforts that can be made by prospective counselors to improve psychological well-being are self-identification, life goals, and collaboration with others.